Translation Shifts in Taylor Swift’s Song Lyrics: An Analysis of Their Translation into Indonesian - Sri, Diana; Made Detriasmita Saientisna; Ni Made Ayu Widiastuti (Universitas Al-Qolam Malang, 2025)
This study aims to identify the types of translation shifts in the Indonesian translations of Taylor Swift’s English song lyrics and to analyse the forms of equivalence applied. The data were collected from three selected songs— “Blank Space,” “Shake It Off,” and “You Belong with Me”—along with their Indonesian translations by digital content writers. A qualitative method with documentation technique was employed. Catford’s (1965) theory of translation shifts, including level and category shifts, and Nida’s (1964) theory of equivalence served as the theoretical framework. Comparative analysis between the source and target texts was conducted to classify translation shifts and assess the equivalence achieved. The study identified a total of 44 translation shifts, with structure shifts being the most frequent, while intra-system shifts were absent. The frequent occurrence of structural and level shifts is attributed to the grammatical differences between English and Indonesian. Dynamic equivalence was more dominant than formal correspondence, indicating that translators prioritized naturalness, clarity, and idiomatic expression, especially for expressive and figurative song lyrics. These findings demonstrate that translation strategies in lyrical texts require careful adaptation of syntax, semantics, and cultural nuances to maintain meaning and aesthetic impact. The study contributes to translation studies by clarifying how translation shifts and equivalence strategies function in creative texts.